Making the most of family remittances : second report (Inter-American Dialogue WashingtonUS, 2007)
Explores how the costs of sending remittances could be reduced further and what could be done to increase the number of migrants and their families in Latin America who have bank accounts. Seeks to find out how Latin American and Caribbean governments could create more productive opportunities for the use of remittances by expanding and improving such public services as health and education. Investigates what would be needed to better understand the macroeconomic impacts of remittances.
Keywords: REMITTANCES